Meta analisis perbandingan luaran prosedur tubeless dan totally tubeless dibandingkan dengan prosedur nefrostomi pasca tindakan percutaneous nephrolithotomy - Oka, Anak Agung Gde (E-Jurnal Medika Udayana, 2020)
Percutaneous nephrolithotomy (PNL) with nephrostomy tube as a drainage has been considered the standard procedure. However, recently many literatures reporting the use of tubeless and totally tubeless as a drainage following PCNL with excellent results. This meta-analysis is aiming to evaluate the safety of tubeless PCNL and totally tubeless PCNL versus nephrostomy tube as a drainage following PNL. All eligible literatures were searched on MEDLINE and Cochrane Library database to identify all randomized controlled trials (RCTs) that compared tubeless and totally tubeless PNL versus nephrostomy tube following PNL. The analyzed outcomes were length of hospital stay, postoperative hemoglobin (Hb) drop, and postoperative analgesic requirements. Review Manager 5.0. was used to conduct the meta-analysis study. Eleven RCTs covering 806 subjects and consist of 9 RCTs for comparison I (tubeless PCNL vs nephrostomy tube PNL, 290 cases and 295 controls) and 2 RCTs for comparison II (totally tubeless PNL vs nephrostomy tube PNL, 113 cases and 108 controls) were identified. Tubeless PNL required significantly less analgesic and shorter length of hospital stay compared with nephrostomy tube PNL. Furthermore, there was shorter length of hospital stay in totally tubeless PNL compared with nephrostomy tube PNL. However, no significant difference was observed in the analyses concerning postoperative Hb decrease in both comparisons. Tubeless PNL and totally tubeless PNL are associated with shorter hospital stay compared with nephrostomy tube PNL. Tubeless PNL also associated with less analgesic requirement compared with nephrostomy tube PNL.